أقسام الأفعال المتعدية في العشرة الأولى من الأحاديث الأربعين النووية وطريقة تعليمها (دراسة تحليلية نحوية) - Kiki Irawan; Angger Putri Mahardini; Nurkholis (Al Mitsali : Jurnal Penelitian dan Pendidikan Bahasa Arab, 2024)
Arabic is a means of understanding Islamic sciences derived from the Qur'an, hadith, and books written in Arabic, therefore understanding this language is very important. And to understand this language must know the rules both nahwu and shorof. Among the discussions of nahwu (Arabic grammatical) is knowing fi'il muta'addi (transitive verb), since some Arabic sentences are composed of it. And this fi'il is found in many of the first ten hadiths of the arbaeen hadiths as each hadith of these hadiths is an extraordinary rule of religious rules that a Muslim should know. The purpose of this study is to find out something related to fi'il muta'addi in the first ten hadiths of the arbaeen hadiths. To get to this goal, researchers use the literature review method which is included in the type of qualitative research. This method is based on searching for data sources, collecting them and analyzing them. And among the results contained in this study are fifty-four fi'il muta'addi (transitive verbs) that require one object, in the 1st hadith (1, 2, 3, 4, 5, 6, 7, 8, 9, 10), and three fi'il muta'addi (transitive verbs) that require two objects, in the 2nd hadith, and two fi'il muta'addi (transitive verbs) that require 3 objects, in the 2nd and 4th hadiths. The learning methods in this study are lecture methods and inductive methods.